Search engines and short video apps as sources of information on acute pancreatitis in China: quality assessment and content assessment - Jiang, Shishuang; Zhou, Youlian; Qiu, Jun; Gou, Xiaohong (Frontiers in Public Health, 2025)
BackgroundAcute pancreatitis is a prevalent condition in China. A plethora of information pertaining to acute pancreatitis is readily available on the Internet, including on major search engines and various short video applications. The objective of this study was to evaluate and compare the quality, content completeness, and accuracy of information related to acute pancreatitis on web pages of the four major search engines and short videos on the two major short video platforms.Materials and methodsA search was conducted on four major search engines (Bing, Baidu, Haosou, and Sougou) and two short video apps (TikTok and BiliBili) using the Chinese keyword “acute pancreatitis.” The sources can be divided into four categories: scientific resources, news/media reports, industrial/commercial profit organizations, and healthcare providers. The quality of the web pages and short videos was evaluated using the DISCERN instrument, the Global Quality Score (GQS), and the Journal of the American Medical Association (JAMA). In accordance with established guidelines and reviews of acute pancreatitis, two lists and scoring systems were devised for the evaluation of content comprehensiveness and accuracy.ResultsA total of 120 unique web pages and 120 unique videos were identified using four search engines and two short video applications, respectively. The most prevalent identity among those producing short videos was that of healthcare providers. With regard to the source of the web pages, the most prevalent category was that of industrial/commercial profit organizations. The median DISCERN total score, median GQS score, and median JAMA score were 26, 3, and 2, respectively. Web pages exhibited significantly higher ratings than short videos (p < 0.001, p = 0.003, and p < 0.001). The median overall content score for the web page was 8 (interquartile range [IQR] 4–13), and the median guideline-related score was 2 (IQR 0–4), indicating that the web page’s content was deficient in terms of completeness and accuracy. In comparison, the performance of the short video was found to be even more deficient.ConclusionIn China, most web pages pertaining to acute pancreatitis were produced by industrial/commercial profit organizations, but the quality of the information provided by these entities was found to be the lowest. The majority of short videos were created by healthcare providers, but the overall quality of these videos was found to be inadequate. In general, the quality of both web pages and short videos is suboptimal. Nevertheless, the quality of web pages was found to be superior to that of short videos. In terms of completeness and accuracy, both the web page and the video exhibit significant deficiencies that are cause for concern.